The FCC’s Abandonment of Sponsorship Identification Regulation & Anonymous Special Interest Group Political Advertising - Sushma Raju (Washington University Law Review, 2016)
Over the course of the last several American election seasons, both political news coverage and political advertising have become all but inescapable. Particularly as election time nears, voters are bombarded by political ads that present highly persuasive, one-sided, and sometimes misleading information about candidates and their platforms. Since the 1920s, federal law, enforced by the Federal Communications Commission (“FCC” or “the Commission”), required broadcasters to identify on-air content as paid political advertisements and to name the sponsors behind the message. At their core, these laws attempt to serve an important purpose: namely, clueing voters in to the identities of the special interest groups pouring millions of dollars into elections behind their candidate of choice. In the last 90 years, however, sponsorship identification law and the FCC’s enthusiasm for enforcement has changed significantly. Today, the FCC’s legal interpretations render the law effectively toothless. To understand the evolution of the law to where it currently stands, this Note reviews the history of sponsorship identification regulation from the 1920s to the present. This historical survey concludes with an analysis of two enforcement actions handled by the FCC in 2014, which supports the argument that the Commission has steadily whittled away the responsibilities that broadcasters have to keep voters informed. The implications of the FCC’s non-enforcement of sponsorship identification law are serious. A review of psychological research indicates political ads are influential in American elections, and voters do consider a sponsor’s identity in determining whether to allow a political ad to affect their vote. Because of the FCC’s current stance, voters get little helpful information as to who is behind the ads they see, making it all the more difficult to sift through the ceaseless torrent of political messaging. In short, when election day arrives, voters are more likely to come to the ballot box misinformed.
Keywords: Federal Communications Commission; FCC; Special interest groups; Political advertising; Political ads; Dark money; Administrative Law; Communications Law